Human Vulnerability Index: Adaptation and Alleviation to Climate Change among Fishing Communities in India’s Bay of Bengal Region - K, Sumankalyani; Ravisankar, H.; Kasturikrishna, S. (Geography, Earth Science and Environment: Research Highlights Vol. 9, 2025)
Climate change involves complex interactions and changing likelihoods of diverse impacts. Climate change may alter the frequency and intensity of extreme events like floods, droughts, heat waves, and hurricanes, but difficult to attribute to anthropogenic climate change. Evidence of climate change impact is the strongest and most comprehensive for natural systems. Impacts on human systems have also been attributed to climate change, with a major or minor contribution of climate change distinguishable from other influences. The objective of the present study is to identify the intensity of the human vulnerability to climate change in a multi-dimensional context. The study area is located along the coastline 20-30 m above sea level on the southeast coast of the Indian Peninsula, bordered by the Bay of Bengal and severely prone to cyclonic occurrences, namely Hudhud, Phailin, and Vardah. A track of cyclonic disturbances, cyclones, and severe cyclones over the Bay of Bengal (BOB) was observed from 1994 to 2015. The study was commissioned as a part of the national project, National Innovations on Climate Resilient Agriculture (NICRA), Indian Council of Agricultural Research (ICAR) during the year 2017. The impact of climate change on the livelihood of the fishing community was measured through an integrated Human Vulnerability Index (HVI) approach. The domain-specific HVI was found to be high for livelihood followed by climate variability, economic, socio-demographic, and health dimensions. In the present study of assessment of the vulnerability index of fisher communities, vulnerability was found to be high for the livelihood dimension followed by climate variability, economic, socio-demographic, and health dimensions.